Dyestuffs, Volume 25 Number 5 - Allied Chemical & Dye Corporation. National Aniline Division (1924)
Fifth issue from the twenty-fifth volume of Dyestuffs, a journal publication from the National Aniline Division of the Allied Chemical & Dye Corporation issued on a monthly to quarterly basis from 1898 to 1964 (suspended briefly from 1916 to 1917). The journal contains reprints of select articles from periodicals in the dyeing and textile fields. This issue contains articles such as Notes on Level Dyeing and Penetration of Cotton Fabrics by Louis J. Matos; Mold and Mildew by A. H. Reiners from Textile World; Regulating Dye Temperature by William Orsted from Textiles; The History of Leather in America; and Causes of Deterioration of Color in Pulp and Paper by Martin L. Griffin from The Paper Trade Journal. This issue includes black and white printed illustrations. Allied Chemical & Dye Corporation (later Allied Corporation, AlliedSignal Inc., and extant today as Honeywell, Inc.), formed in 1920 as an amalgamation of five chemical companies including the National Aniline & Chemical Company (founded 1917), Semet-Solvay Company (founded 1895), and the Solvay Process Company (founded 1881).
Keywords: Dyes and dyeing; Periodicals; Allied Chemical & Dye Corporation. National Aniline Division; Dyes and dyeing--Chemistry; Dyes and dyeing--Textile fibers; Textile fabrics; Textile industry